2017
DOI: 10.5194/amt-10-4373-2017
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and correction of OMPS nadir mapper measurements for ozone profile retrievals

Abstract: Abstract. This paper verifies and corrects the Ozone Mapping and Profiler Suite (OMPS) nadir mapper (NM) level 1B v2.0 measurements with the aim of producing accurate ozone profile retrievals using an optimal-estimation-based inversion method to fit measurements in the spectral range 302.5-340 nm. The evaluation of available slit functions demonstrates that preflight-measured slit functions represent OMPS measurements well compared to derived Gaussian slit functions. Our initial OMPS fitting residuals contain … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
36
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 37 publications
(38 citation statements)
references
References 44 publications
0
36
0
Order By: Relevance
“…Figure 1 is a schematic diagram of the ozone profile algorithm. With the input of satellite measurements, the slit function is parameterized through cross-correlation between satellite irradiance and a high-resolution solar reference spectrum to be used for wavelength calibration and for high-resolution cross section convolution (Sun et al, 2017;Bak et al, 2019); a normalized Gaussian distribution is assumed to derive analytic slit functions for OMI. To remove the systematic errors between measured and calculated radiances, "soft calibration" is applied to measured radiances and then the logarithms of sun-normalized radiances are calculated as measurement vectors (Liu et al, 2010a;Cai et al, 2012;Bak et al, 2017).…”
Section: Ozone Profile Retrievalsmentioning
confidence: 99%
“…Figure 1 is a schematic diagram of the ozone profile algorithm. With the input of satellite measurements, the slit function is parameterized through cross-correlation between satellite irradiance and a high-resolution solar reference spectrum to be used for wavelength calibration and for high-resolution cross section convolution (Sun et al, 2017;Bak et al, 2019); a normalized Gaussian distribution is assumed to derive analytic slit functions for OMI. To remove the systematic errors between measured and calculated radiances, "soft calibration" is applied to measured radiances and then the logarithms of sun-normalized radiances are calculated as measurement vectors (Liu et al, 2010a;Cai et al, 2012;Bak et al, 2017).…”
Section: Ozone Profile Retrievalsmentioning
confidence: 99%
“…The development of the GEMS ozone profile algorithm builds on heritages of the Smithsonian Astrophysical Observatory (SAO) ozone profile algorithm which was originally developed for GOME (Liu et al, 2005), continuously adapted for its successors such as OMI (Liu et al, 2010a), GOME/2 (Cai et al, 2012), and OMPS (Bak et al, 2017). In addition, the SAO algorithm will be implemented to retrieve TEMPO ozone profiles (Chance et al, 2013;Zoogman et al, 2017).…”
Section: Ozone Profile Retrievalsmentioning
confidence: 99%
“…The described OE-fitting solution can be written, together with cost function χ : (Bak et al, 2013a). and high-resolution solar reference spectrum to be used for wavelength calibration and for highresolution cross section convolution (Sun et al, 2017;Bak et al, 2017); normalized Gaussian distribution is assumed to derive analytic slit function for OMI. To remove the systematic errors between measured and calculated radiances, "soft-calibration" is applied to measured radiances and then the logarithm of sun-normalized radiances is calculated as a measurement vector (Liu et al, 2010a;Cai et al, 2012;Bak et al, 2017).…”
Section: Ozone Profile Retrievalsmentioning
confidence: 99%
See 1 more Smart Citation
“…Global distributions of atmospheric species that play critical roles 5 in atmospheric chemistry and air pollution, such as ozone (e.g., Bak et al, 2017), NO 2 (e.g., Krotkov et al, 2017), SO 2 (e.g., Li et al, 2017a), formaldehyde (HCHO, e.g., González Abad et al, 2015), glyoxal (CHOCHO, e.g., Chan Miller et al, 2014), and BrO (e.g., Suleiman et al, 2018), have been retrieved from the backscattered solar UV-visible spectra observed by generations of polar-orbiting satellite sensors, including GOME , SCIAMACHY (Bovensmann et al, 1999), OMI (Levelt et al, 2018), GOME-2 (Munro et al, 2016), OMPS (Rodriguez et al, 2003), and TROPOMI (Veefkind et al,10 2012). A constellation of geostationary satellites will provide hourly measurements of these species over North America, Europe, and Asia in the near future (Zoogman et al, 2017).…”
Section: Introductionmentioning
confidence: 99%